Private concerns in public discourse: women-initiated community responses to domestic violence - Bhatla, Nandita; Rajan, Anuradha (2003)
This paper is based on a participatory research study that sought to explore the dynamics of community-based responses to domestic violence across five sites in India. The study was intended to provide documentation of how women-led innovative responses have emerged, how they operate, and how successful they are in addressing the needs of women subject to domestic violence. Community responses to violence can open democratic forms of dispute resolution and to operationalise an objective process through a feminist perspective, incorporating a strong element of preventive justice. - Reproduced.
Keywords: Women; Domestic violence